microRNA (miRNA) speciation in Alzheimer’s disease (AD) cerebrospinal fluid (CSF) and extracellular fluid (ECF) - Alexandrov, Peter N (e-Century Publishing Corporation, 2012)
Human cerebrospinal fluid (CSF), produced by the choroid plexus and secreted into the brain ventricles and subarachnoid space, plays critical roles in intra-cerebral transport and the biophysical and immune protection of the brain. CSF composition provides valuable insight into soluble pathogenic bio-markers that may be diagnostic for brain disease. In these experiments we analyzed amyloid beta (Aβ) peptide and micro RNA (miRNA) abundance in CSF and in short post-mortem interval (PMI <2.1 hr) brain tissue-derived extracellular fluid (ECF) from Alzheimer’s disease (AD) and age-matched control neocortex. There was a trend for decreased abundance of Aβ42 in the CSF and ECF in AD but it did not reach statistical significance (mean age ~72 yr; N=12; p~0.06, ANOVA). The most abundant nucleic acids in AD CSF and ECF were miRNAs, and their speciation and inducibility were studied further. Fluorescent miRNA-array-based analysis indicated significant increases in miRNA-9, miRNA-125b, miRNA-146a, miRNA-155 in AD CSF and ECF (N=12; p<0.01, ANOVA). Primary human neuronal-glial (HNG) cell co-cultures stressed with AD-derived ECF also displayed an up-regulation of these miRNAs, an effect that was quenched using the anti-NF-кB agents caffeic acid phenethyl ester (CAPE) or 1-fluoro-2-[2-(4-methoxy-phenyl)-ethenyl]-benzene (CAY10512). Increases in miRNAs were confirmed independently using a highly sensitive LED-Northern dot-blot assay. Several of these NF-кB-sensitive miRNAs are known to be up-regulated in AD brain, and associate with the progressive spreading of inflammatory neurodegeneration. The results indicate that miRNA-9, miRNA-125b, miRNA-146a and miRNA-155 are CSF- and ECF-abundant, NF-кB-sensitive pro-inflammatory miRNAs, and their enrichment in circulating CSF and ECF suggest that they may be involved in the modulation or proliferation of miRNA-triggered pathogenic signaling throughout the brain and central nervous system (CNS).